Novel flow reactor for handling suspensions: hydrodynamics and performance evaluation - Sharma, Mrityunjay K.; Suru, Aditya; Joshi, Anuj; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2020)
A novel reactor concept that can handle solid particles without any moving components in the reactor is proposed and demonstrated in this work. The proposed reactor is designed by arranging the unique shape cavities in a sequence where inlet and outlets are positioned off-center to each other at specific angles and distance. Detailed flow simulation suggested that cavities with diameter D, having aspect ratio H/D similar to 1.53, outlet (having a diameter of 0.2D) positioned at 0.3D from the center and at 180 degrees with reference to the inlet is suitable for the expected performance. The proposed geometry of the reactor with the optimal geometrical configuration was fabricated and hydrodynamics (viz. pressure drop, mass transfer, and heat transfer, and residence time distribution) were studied. The reactor also offered high mass transfer coefficients and is useful for liquid-liquid reactions and extraction. A variety of solid suspensions (glass particles, activated carbon, starch particles, magnesium hydroxide) were tested over a wide range of flow rates for checking the solid handling capability of the reactor. The neutralization reaction of NaOH (with dissolved a-naphthol) with concentrated HCl that results in almost instantaneous precipitation of a-naphthol from the solution is used as a test reaction for a range of a-naphthol concentrations to change the suspension loading. It is shown that the proposed reactor can handle up to 22% (w/v) solid concentration without any clogging for a longer duration of the operation. However, for sticky solid particles, the same reactor would get clogged at the outlet ports for smaller diameters.